Core–Shell‐Type Magnetic Mesoporous Silica Nanocomposites for Bioimaging and Therapeutic Agent Delivery. (19th September 2014) - Wang, Yao; Gu, Hongchen
<x xml:space="preserve">Abstract</x> Advances in nanotechnology and nanomedicine offer great opportunities for the development of nanoscaled theranostic platforms. Among various multifunctional nanocarriers, magnetic mesoporous silica nanocomposites (M‐MSNs) attract prominent research interest for their outstanding properties and potential biomedical applications. This Research News article highlights recent progress in the design of core–shell‐type M‐MSNs for both diagnostic and therapeutic applications. First, an overview of synthetic strategies for three representative core–shell‐type M‐MSNs with different morphologies and structures is presented. Then, the diagnostic functions of M‐MSNs is illustrated for magnetic resonance imaging (MRI) applications. Next, magnetic targeted delivery and stimuli‐responsive release of drugs, and effective package of DNA/siRNA inside mesopores using M‐MSNs as therapeutic agent carriers are discussed. The article concludes with some important challenges that need to be overcome for further practical applications of M‐MSNs in nanomedicine.